Halogen emissions from a small volcanic eruption: modeling the peak concentrations, dispersion, and volcanically induced ozone loss in the stratosphere - Millard, G; Mather, T; Pyle, D; Rose, W; Thornton, B (Geophysical Research Letters, 2016)
Aircraft measurements in the Hekla, Iceland volcanic plume in February 2000 revealed large quantities of hydrogen halides within the stratosphere correlated to volcanic SO₂. Investigation of the longer-term stratospheric impact of these emissions, using the 3D chemical transport model, SLIMCAT suggests that volcanic enhancements of H₂O and HNO₃ increased HNO₂ 3H₂O particle availability within the plume. These particles activated volcanic HCI and HBr, enhancing model plume concentrations of ClOₓ (20 ppb) and BrOₓ (50 ppt). Model O₃ concentrations decreased to near-zero in places, and plume average O₃ remained 30% lower after two weeks. Reductions in the model O₃ column reduced UV shielding by 15% for 2 days. Plume incorporation into the winter polar vortex after 1 March elevated model vortex Cl[sub>y and Br[sub>y by 0.15 ppb and 7 ppt respectively, and doubled vortex ClOₓ and BrO. Model results agree quantitatively with the observations made by the DC-8 aircraft.